2020
DOI: 10.1021/acs.jpclett.0c02452
|View full text |Cite|
|
Sign up to set email alerts
|

Density Functional Theory for Molecule–Metal Surface Reactions: When Does the Generalized Gradient Approximation Get It Right, and What to Do If It Does Not

Abstract: While density functional theory (DFT) is perhaps the most used electronic structure theory in chemistry, many of its practical aspects remain poorly understood. For instance, DFT at the generalized gradient approximation (GGA) tends to fail miserably at describing gas-phase reaction barriers, while it performs surprisingly well for many molecule–metal surface reactions. GGA-DFT also fails for many systems in the latter category, and up to now it has not been clear when one may expect it to work. We show that G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(111 citation statements)
references
References 111 publications
(219 reference statements)
2
94
0
Order By: Relevance
“…This implies a more rigorous understanding of the spin (charges) density redistribution induced by the interaction of water entities with carbon structures. Although it is frequently used in the description of the electronic structure of a system, DFT based on the generalized gradient approximation has certain limitations, in particular for the modeling of chemical reactions [ 58 ] and the estimation of gas-phase energy barriers [ 59 ]. DFT-GGA may also not work well for many molecule–metal surface reactions and for van der Waals adsorption on surfaces [ 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…This implies a more rigorous understanding of the spin (charges) density redistribution induced by the interaction of water entities with carbon structures. Although it is frequently used in the description of the electronic structure of a system, DFT based on the generalized gradient approximation has certain limitations, in particular for the modeling of chemical reactions [ 58 ] and the estimation of gas-phase energy barriers [ 59 ]. DFT-GGA may also not work well for many molecule–metal surface reactions and for van der Waals adsorption on surfaces [ 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…ref. [348][349][350], and a screened hybrid DF has already been used in dynamics calculations on O 2 + Al( 111) 351 (see below). The B3LYP DF is the best known global hybrid DF 352 in which the exchange energy is a mixture of exact exchange (20%) and GGA exchange, 313 and GGA correlation 353 (the DF is therefore called a hybrid GGA DF).…”
Section: See Below)mentioning
confidence: 99%
“…Very recently QCT calculations have been performed 351 on O 2 + Al(111) that used the mGGA MS RPBEl DF 152 discussed earlier and the screened hybrid HSE03-1/3X DF. The HSE03-1/ 3X DF is based on the HSE03 DF 692,693 with the maximum fraction of exact exchange increased from 1/4 to 1/3.…”
Section: H 2 + Pdmentioning
confidence: 99%
“…It has recently been suggested that for reactions where the difference between the surface' work function and the electron affinity of the adsorbate is smaller than 7 eV, DFT-GGA calculations of barrier heights may be unreliable. 371 As seen in Figure 15, it is precisely under these conditions that electronically nonadiabatic coupling between 378 The influence of vibrational excitation on dissociative adsorption was first seen by changing the beam source temperature and seed gas to thermally excite CH 4 vibrations. 380,381 This influence of vibration is more cleanly seen with laser pre-excitation of the molecule, where a molecular beam of methane with controlled translational energy is excited by a c. w. infrared laser with high power and coherence producing selected vibrational states.…”
Section: Vibrational and Translational Promotion Of Surface Reactions H 2 On Coppermentioning
confidence: 98%
“…While the research on this reaction, so far, is no success story, it is without doubt one of the most interesting for future study. It has recently been suggested that for reactions where the difference between the surface’ work function and the electron affinity of the adsorbate is smaller than 7 eV, DFT‐GGA calculations of barrier heights may be unreliable 371 . As seen in Figure 15, it is precisely under these conditions that electronically nonadiabatic coupling between adsorbate nuclear motion and the solids EHPs may become important.…”
Section: Dynamics Of Reactions At Surfacesmentioning
confidence: 99%